Fotografia 2D e 3D : imagens da interdisciplinaridade entre arte e ciência - Damiani, Vitor (2016)
The history of photography is permeated with technological breakthroughs that enabled the development of concepts in different areas and wide artistic expression. In this work, the photography is used as a conversion method from 2D images to 3D digital models that are subject to interventions and manipulations in order to produce an artistic object. The aforementioned method already exists, but another aspect of photography has important value here: the description of the movement through images and its many forms of representation (such as a trail, blur or absence of matter). A question arose: could such a blur be inherited from the bidimensionality of the long exposure photography into a real, touchable object? What are the media-related implications and how could the artist use this methodology to his visual expression? By using concepts of chronophotography, cubist glimpses, cinematic techniques like stop-motion and new technologies, we explore the transposition from image-related aspects into real tridimensional representations, with the use of 3D printing. The results of this work are artistic objects that represent the materialization of the movement in the photography into a real object. Nevertheless, the possibilities go beyond: graduated transparency and large-scale 3D prints, production of non-human forms and customized motion capture as the objects’ motion source. Therefore, the knowledge produced brings contributions that can be used in other researches: the applied methodology can be re-used (as well as for other purposes) in various areas of knowledge, both for artistic creations and scientific applications.